Hibernoma Mimicking Atypical Lipomatous Tumor: 64 Cases of a Morphologically Distinct Subset. (July 2018) - Al Hmada, Youssef; Schaefer, Inga-Marie; Fletcher, Christopher D.M.
Abstract : Hibernoma is a benign adipocytic tumor with predilection for subcutaneous tissue of the thigh, upper trunk, and neck of middle-aged adults. 11q13 rearrangement resulting in MEN1 / AIP codeletion is characteristic. Hibernomas are composed, in varying proportions, of brown fat cells, mature adipocytes, and microvacuolated lipoblast-like cells. Examples containing predominantly multivacuolated lipoblast-like cells are uncommon and distinction from atypical lipomatous tumor (ALT) is important for clinical management. We herein present the clinicopathologic features of 64 hibernomas histologically mimicking ALT. MDM2 and CDK4 immunohistochemistry as well as MDM2 fluorescence in situ hybridization were performed in a subset of cases. Clinical and follow-up information were obtained from referring pathologists. Thirty-four patients were male and 30 female, with a median age of 43 years (range, 24 to 78 y). The tumors were well circumscribed and mostly deeply located (53/64 cases, 83%) with a median tumor size of 12.9 cm (range, 3.5 to 23 cm) and predilection for the thigh (42/64 cases, 66%). Histologically, large cells with prominent lipoblast-like cytoplasmic fatty vacuoles and small central nuclei were present to a prominent degree in all cases, along with mature univacuolated adipocytes and smaller numbers of large, finely vacuolated cells with eosinophilic granular cytoplasm. Nuclear atypia and mitoses were absent. None of the 39 cases tested showed CDK4 and MDM2 overexpression or MDM2 amplification. Follow-up, available for 16/64 cases (median, 47 mo; range, 1 to 165 mo), revealed no recurrences or metastases. Hibernoma mimicking ALT shows predilection for deep soft tissue, especially in the thigh. These tumors behave in a benign manner and MDM2/CDK4 negativity may be useful in excluding ALT.